RANCANG BANGUN SISTEM E-ADMINISTRASI BERBASIS CODEIGNITER FRAMEWORK DI KP2A BATAM - Lim, Nurfitra Efriansyah; Silalahi, Mesri (Computer Science and Industrial Engineering, 2023)
This study aims to design and build an e-administration information system based on the CodeIgniter framework at KP2A Batam to solve administrative problems. Some of the administrative services currently being carried out by KP2A are registration of prospective students who wish to join KP2A, payment of monthly course fees, payment of book fees, photocopy fees, and expenses. The problem currently being faced by KP2A is in its administrative activities, starting from the admin recording the names of prospective students on paper, recording payment for books on paper, recording photocopy costs on paper, and recording expenses used to support teaching activities. everything is done by hand. The problem that often arises is one of them is the payment of fees that are not by the truth or a partial payment arises. From these problems, an e-administration information system was built that can make stored old and new data more organized and safer, prevent partial payment problems, and reduce errors in reporting. The method used is SDLC with the development of an agile scrum model. Research is expected to have a positive impact on readers, writers, and research objects.